An acoustic method for the evaluation of the state of the larynx source in cases involving pathological changes in the vocal folds - GYBRYNOWICZ, Ryszard; MIKIEL, Władysław; ŻARNECKI, Piotr (Archives of Acoustics, 1980)
With a view to discussion of the role of the larynx source in the formation of the acoustic speech signal, this paper presents a method for the evaluation of the state of the larynx for different pathological states of the vocal chords. 143 persons, both healthy and with specific pathological voice changes were investigated. The pathological conditions included unilateral and bilateral paralysis of the larynx nerves, inflammation states and cancerous development, both benign (polyps, papillomas etc.) and malignant. For the analysis of the speech signal an Intonograph-77 was used, which together with a ME RA-300 minicomputer provides an integral system for automatic measurement and registration of the values of successive periods of the larynx tone, currently determined, during the articulation of longer texts. The evaluation of the state of the larynx source was performed on the basis of the analysis of the phonation time and the statistical distributions of the values of periods of the larynx excitation and their percentage changes in time. A final evaluation was performed, using a diagnostic model in which fuzzy relations were used for the classification of voices into two sets-normal and pathological voices. The mean classification error did not exceed 8%, with a lack of decision occurring in about 20% of the casses.